2011
DOI: 10.1590/s0001-37652011000200020
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood transfusion in small animals: indications and effects

Abstract: Transfusion therapy is a major resource that can improve the patient's capability to overcome the underlying disease. However, the effects of whole blood infusion, and how they affect the patient's outcome, are not yet clear. For this study, a protocol was developed in order to monitor a group of 15 animals (9 dogs, 6 cats) that received a total of 19 transfusions; 3 animals received more than one transfusion each. The most common indications for blood transfusion included acute blood loss (47%), coagulopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 12 publications
4
21
0
Order By: Relevance
“…Large-and giantbreed dogs are often deep chested, making observation of organs in the thorax and cranial portion of the abdomen more difficult. 5,22,23 In the present study, survival rate at 2 weeks after surgery was inversely related to perioperative blood transfusion, meaning that those dogs undergoing perioperative RBC transfusion had a decreased chance of surviving to 2 weeks after surgery. Obesity is an accepted risk factor for increased surgical difficulty because excess adipose tissue may impede the surgeon' s ability to view the surgical site and may also contribute to the slippage of ligatures.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Large-and giantbreed dogs are often deep chested, making observation of organs in the thorax and cranial portion of the abdomen more difficult. 5,22,23 In the present study, survival rate at 2 weeks after surgery was inversely related to perioperative blood transfusion, meaning that those dogs undergoing perioperative RBC transfusion had a decreased chance of surviving to 2 weeks after surgery. Obesity is an accepted risk factor for increased surgical difficulty because excess adipose tissue may impede the surgeon' s ability to view the surgical site and may also contribute to the slippage of ligatures.…”
Section: Discussionsupporting
confidence: 46%
“…Although the only significant differences in mean body weight were found between patients undergoing partial gastrectomy and partial gastrectomy and splenectomy and those undergoing perineal herniorrhaphy, the lack of significant differences in mean body weight among all surgical types may reflect sample size and within-category variation. In another study by Godinho-Cunha et al, 23 15 dogs and cats received 19 RBC transfusions, and 60% survived to discharge from the hospital. Large-and giantbreed dogs are often deep chested, making observation of organs in the thorax and cranial portion of the abdomen more difficult.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is similar to a previous study (Godinho‐Cunha et al . ), in which lower survival rates were observed in dogs and cats after receiving blood transfusions due to acute blood loss. In the present study, a variety of causes were identified within the group of cats with anaemia due to blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…, Godinho‐Cunha et al . ). While pre‐transfusion blood type compatibility testing is standard before any feline blood transfusion (Bücheler & Giger ), other pre‐transfusion testing is not performed as frequently.…”
Section: Introductionmentioning
confidence: 97%